The Eclectic Approach on One-To-One Teaching Indonesian for Foreigner - Hanna Sundari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
Indonesian has been considerably preferred and extensively taught by many foreigners for various causes and purposes so that its teaching (Indonesian for foreigners or BIPA) has attracted more attention and wide studies in the field of foreign language instruction. One of approaches in language classroom is eclectic approach. This paper tries to describe the implementation of the principles of eclectic approach for one-to-one teaching Indonesian for foreigner. The participants were one Indonesian tutor and one Australian tutee who managed 14 meetings for teaching sessions. Using descriptive qualitative research design, teacher/course notes, worksheets, and learning materials were collected, analyzed, and interpreted. Moreover, open-ended questionnaire was to gather of how the approach was implemented. The findings show that the eclectic practices cover communicative tasks, regular dialogues, using authentic materials, integration of language skills and component as well as deductive grammar and vocabulary building. And it is a combination of three well-known language teaching methods. Keywords: eclectic approach, BIPA, one-to-one teaching